Observation of ZZ Production in p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Mundim, L.; et al. (Amer Physical Soc, 2008)
We present an observation for ZZ -> l(+) l(-) l'(+) l'(-) (l, l' =e or mu) production in p (p) over bar collisions at a center-of-mass energy of root s = 1.96 TeV. Using 1.7 fb(-1) of data collected by the D0 experiment at the Fermilab Tevatron Collider, we observe three candidate events with an expected background of 0.14(-0.02)(+0.03) events. The significance of this observation is 5.3 standard deviations. The combination of D0 results in this channel, as well as in ZZ -> l(+) l(-) v (v) over bar yields a significance of 5.7 standard deviations and a combined cross section of sigma(ZZ) = 1.60 +/- 0.63(stat)(-0.17)(+0.16)(syst) pb.